Understanding Customer Behavior In An Online Travel Agent: The Influence of Gender, User’s City Location, and Loyalty Status towards Promotion Usage during COVID-19 Pandemic - Cindy Cendana; Hendra Achmadi (Budapest International Research and Critics University, 2022)
With the rising popularity of online activity and state-of-the-art technology these past few years, it is only natural that the travel agency industry has shifted its focus from offline to online selling. Rising demand for online travel purchases means Online Travel Agent (OTA) needs to stay competitive in the industry. Moreover during COVID-19 it is becoming more important to stay competitive. Among all of the 50 plus online travel agencies in Indonesia, there are several that are bigger than the others; these include Traveloka and tiket.com. One of the strategies that these companies implement to stay competitive is giving out promotion vouchers; however, do they really work for all of their customers? In order to best understand OTA customers, this research analyzes the impacts of gender, city demographic, and the user’s loyalty status in an Indonesian Online Travel Agent on each customer’s usage on promotion vouchers. Data was collected from tiket.com’s database. The findings will provide evidence as to whether the gender, user’s city location, and the loyalty member status have a positive effect on promotion voucher usage in an Online Travel Agent.